Vascular endothelial function assessed by a noninvasive ultrasound method and serum asymmetric dimethylarginine concentrations in mild-to-moderate plaque-type psoriatic patients - ALİBAZ ÖNER, FATMA (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
Objectives: Our aim was to evaluate vascular endothelial function assessed by serum asymmetric dimethylarginine (ADMA) concentrations and noninvasive ultrasonographic parameters such as flow-mediated dilatation (FMD) and nitroglycerin-induced dilatation (NID) in mild-to-moderate plaque-type psoriatic patients, as rated by the Psoriasis Area and Severity Index. Design and methods: Plaque-type psoriatic patients (n = 29) diagnosed with clinical and/or histopathological findings and control subjects (n = 25) without skin and systemic metabolic diseases were included in the study. Results: There was no statistically significant difference between patients and control subjects in respect to FMD (p = 0.441), NID (p = 0.557), or serum ADMA concentrations (p = 0.225). Also, among the acute-phase reactants, serum C-reactive protein and plasma fibrinogen levels were moderately higher in patients when compared to control subjects (p = 0.008 and p = 0.011, respectively). Conclusions: Mild-to-moderate plaque-type psoriatic patients with low-to-medium grade systemic inflammation did not have evidence of vascular endothelial function. (C) 2011 The Canadian Society of Clinical Chemists. Published by Elsevier Inc. All rights reserved.
Keywords: Brachial artery; Dimethylarginine; Endothelium; Psoriasis